Investigation of exceptionally radar-dark regions on the lunar nearside - Tveito, Torbjørn; Vierinen, Juha; Serrano, Alessandra (2019)
Presentation at the 19th International EISCAT Symposium 2019 and 46th Annual European Meeting on Atmospheric Studies by Optical Methods, Oulu, Finland, 19.08. - 23.08.19, arranged by the University of Oulu. ( http://www.sgo.fi/Events/EISCAT46AM/). Remote sensing of planetary surfaces is an effective method for gaining knowledge of the processes that shape the planetary bodies in our solar system. This is useful for uncovering the environment of the primordial solar system and to study the current state of the upper crusts of the other planets in our neighborhood. A recent 6-meter wavelength polarimetric radar map of the Moon [?] showed unexpectedly low depolarized radar returns in two regions on the lunar nearside. These two areas were a highland region between Mare Imbrium and Mare Frigoris, and the highland area surrounding the Schiller-Zucchius impact basin. These two regions showed characteristics unlike those of typical highland regions of the lunar surface. So far, there has been no readily available explanation for this observation. In this study, it is shown that the likely cause is an increased loss tangent due to chemical differences in the first few hundred meters of the lunar soil. We also show the absence of any coherent subsurface, which could be the preserved remains of an ancient basaltic plain. We do this by comparing the 6-meter polarimetric radar map to other relevant data sets: 1) surface TiO2 and FeO abundance, 2) surface rock population, 3) radar maps of the Moon with other wavelengths, and 4) visual spectrum images of the Moon. The area near the Schiller-Zucchius basin was shown to be consistent with other areas with similar surface chemical compositions, but the region between Mare Imbrium and Mare Frigoris showed significantly lower mean power in comparison to otherwise similar regions. While we can not conclusively determine the cause, we hypothesize that the low radar return is explained by an increased concentration of iron and titanium oxides in the volume beneath the surface, ...